Getting your message across - Hanks, Kurt (Crisp Pub. Menlo ParkUS, 1991)
Presents general principles, methods and concepts designed to increase communication effectiveness. Includes 8 kinds of sequences for use in planning presentations, and warns against overloading audience with information. Provides guidelines for getting the attention of the audience and maintaining their interest. Suggests techniques including: preparing the audience for the presentation; and linking the presentation to the previous knowledge and experience of the audience.